OXYGEN AND HYDROGEN ISOTOPE VARIATIONS IN A RECENTLY FORMED MASSIVE ICE AT THE MOUTH OF THE AKKANI RIVER, EASTERN CHUKOTKA - Yu. K. Vasil'chuk; Ju. N. Chizhova; A. A. Maslakov; N. A. Budantseva; A. C. Vasil'chuk (Лëд и снег, 2018)
The object of this study is a recently (or in the Holocene) formed thick (up 2.7 m in height) buried massive ice body, exposed in 2 km South-East from the mouth of the river Akkani in the North-East of Chukotka in the vicinity of the settlement Lavrentiya. The structural-textural characteristics of ice and enclosing deposits are considered. It is shown that the overlying layers of sediments are loams with a slab structure and vertical-layer medium and thin-chill cryogenic structure and ice sockets. The ice of the body is very pure and transparent, visible to a depth of 0.5 m. There are some inclusions found in massive ice: sand and loams presented in forms of thin interlayers of particles or granules. The ice is full of bubbles. The main method of the research was the analysis of isotopes of oxygen and hydrogen within the stratified ice body, and also relationships between them as well as ratios between the deuterium excess and δ2Н. The thick and relatively contemporary massive ice layer buried under a layer of proluvial sediments had been found for the first time, and together with this, the isotope variations of the buried ice (δ2Н and δ18O) were determined. The mean values of δ18О and δ2H in the ice are rather stable and equal to −17.1 and −128.3‰, respectively. These isotope characteristics may be used for cryogenic reconstructions of massive ice formations widely distributed in the late Quaternary deposits in Eastern Chukotka.